Factors on Community Investment-Based Small Scale Irrigation Development in Indonesia: Case of West Nusa Tenggara - Nur Suhaeti, Rita; Saleh, Amiruddin; Abbas, Akmadi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
ABSTRACTCommunity-based investment for small-scale irrigation (CISI) was one of the opportunities to increase food production, mainly rice, to support food security at household and national levels. Social capital played a crucial role in small irrigation management allowing all water distribution with appropriate criteria, amount and time for all farmers within the irrigation network. Therefore it was necessary to investigate various influencing factors on investment development and financial viability in a small irrigation system. The research used survey method with indepth group discussion. Data were analyzed descriptively. Government’s ignorance and less wise for community self-help and social capital has caused a dependency to Government’s aids. Water User’s Association (WUA) institutional for small irrigation was definitely considered important in managing irrigation water. Social capital was formed and interacted with natural capital and human capital and framed in group social relationships. Leadership providing good exemplary, fair, honest, trustworthy, sincerity and well-being oriented was needed. WUA empowerment was necessary and crucial in order to get more fair irrigation water distribution. The CISI financial feasibility was strongly determined by benefits derived from the irrigation construction such as planted rice acreage increase. The CISI benefits were determined by community’s ability to perform maintenance investment.Keywords: community’s investment-based, small scale irrigation system, social capitalABSTRAKIrigasi skala kecil berbasis investasi masyarakat (IKBIM) merupakan salah satu peluang untuk meningkatkan produksi pangan, terutama beras, untuk mendukung ketahanan pangan di tingkat rumah tangga dan nasional. Modal sosial memainkan peran penting dalam pengelolaan irigasi kecil yang memungkinkan semua distribusi air dengan kriteria, jumlah dan waktu yang tepat untuk semua petani di dalam jaringan irigasi. Oleh karena itu perlu dilakukan penelitian untuk mengetahui berbagai faktor yang mempengaruhi perkembangan investasi dan kelayakan finansial dalam sistem irigasi kecil. Penelitian menggunakan metode survei dengan diskusi kelompok secara mendalam. Data dianalisis secara deskriptif. Ketidaktahuan dan kekurangbijaksanaan pemerintah dan untuk swadaya masyarakat dan modal sosial telah menyebabkan ketergantungan petani pada bantuan Pemerintah. Perhimpunan Petani Pemakai Air (P3A) untuk irigasi kecil memang dianggap penting dalam pengelolaan air irigasi. Modal sosial dibentuk dan berinteraksi dengan modal alam dan modal manusia dan dibingkai dalam hubungan sosial kelompok. Kepemimpinan memberikan teladan, adil, jujur, dapat dipercaya, tulus dan berorientasi pada kebutuhan. Pemberdayaan P3A diperlukan dan penting untuk mendapatkan distribusi air irigasi yang lebih adil. Kelayakan finansial IKBIM sangat ditentukan oleh manfaat yang berasal dari konstruksi irigasi seperti kenaikan areal tanam padi. Manfaat IKBIM ditentukan oleh kemampuan masyarakat untuk melakukan investasi pemeliharaan.Kata kunci: modal berbasis masyarakat, modal sosial, sistem irigasi skala kecil